Do Alternative Dispute Resolution (ADR) and Track Two Processes Support Transboundary Marine Conservation? Lessons From Six Case Studies of Maritime Disputes - Teff-Seker, Yael; Mackelworth, Peter C.; Vega Fernández, Tomás; McManus, John; Nam, Jungho; Tuda, Arthur O.; Holcer, Drasko (Frontiers in Marine Science, 2020)
By definition, marine protected areas (MPAs) and other effective area-based conservation measures (OECMs) address spatial aspects of the ecological processes and marine features. Such a requirement is especially challenging in areas where there is no clearly defined jurisdiction. However, in these areas, assigning sovereignty and rights can be achieved through bilateral or multilateral agreements, or with the use of alternative dispute resolution (ADR) tools such as mediation and arbitration. In some cases, states may engage in transboundary marine conservation initiatives to provide an entry point to enable wider collaboration. These processes can also evolve into a form of ‘environmental peacebuilding’ while ideally maintaining ecosystem functioning and resilience as a core goal. Conversely, MPAs and OECMs can also be used to assert maritime sovereignty rights over disputed waters, under the pretext of conserving marine habitats. This paper identifies emerging issues of conflict resolution and their interaction with transboundary marine conservation. While ADR focuses on negotiations and facilitated processes between state representatives (“track one diplomacy”), we also discuss other forms and levels of marine environmental peacebuilding and dispute resolution, particularly those between civil society organizations (“track two diplomacy”). The six case studies presented highlight areas of recent maritime conflict or border disputes in the Mediterranean Sea, the Red Sea, the West Indian Ocean, the Korean West Sea and the South China Sea. In all cases, high ecological value, vulnerable ecosystems, and the need to conserve ecosystem services provide a shared interest for cooperation despite on-going diplomatic difficulties. The strategies used in these cases are analyzed to determine what lessons might be learned from cross-border collaborative marine initiatives in situations of territorial disputes. The use of ADR tools and their ability to support joint marine initiatives are examined, as well as how such initiatives contribute to formal border negotiations. Other forms of inter-state dialogue and cooperation between local or civil organizations, circumventing formal treaties and negotiations between state leaders (‘track two’) are also investigated. Finally, other influencing factors, including third-party involvement, stakeholder interests, power dynamics, economic context, and socio-cultural aspects, are considered.